Nuprl Lemma : quadratic1-one
∀[a,b,c:ℝ].  (quadratic1(a;b;c) = r1) supposing ((c ≤ a) and (b = -(a + c)) and (r0 < a))
Proof
Definitions occuring in Statement : 
quadratic1: quadratic1(a;b;c)
, 
rleq: x ≤ y
, 
rless: x < y
, 
req: x = y
, 
rminus: -(x)
, 
radd: a + b
, 
int-to-real: r(n)
, 
real: ℝ
, 
uimplies: b supposing a
, 
uall: ∀[x:A]. B[x]
, 
natural_number: $n
Definitions unfolded in proof : 
uall: ∀[x:A]. B[x]
, 
uimplies: b supposing a
, 
member: t ∈ T
, 
sq_stable: SqStable(P)
, 
implies: P 
⇒ Q
, 
squash: ↓T
, 
rneq: x ≠ y
, 
or: P ∨ Q
, 
prop: ℙ
, 
all: ∀x:A. B[x]
, 
iff: P 
⇐⇒ Q
, 
and: P ∧ Q
, 
rev_implies: P 
⇐ Q
, 
less_than: a < b
, 
less_than': less_than'(a;b)
, 
true: True
, 
quadratic1: quadratic1(a;b;c)
, 
subtype_rel: A ⊆r B
, 
uiff: uiff(P;Q)
, 
rev_uimplies: rev_uimplies(P;Q)
, 
req_int_terms: t1 ≡ t2
, 
false: False
, 
not: ¬A
, 
top: Top
, 
guard: {T}
, 
rdiv: (x/y)
Latex:
\mforall{}[a,b,c:\mBbbR{}].    (quadratic1(a;b;c)  =  r1)  supposing  ((c  \mleq{}  a)  and  (b  =  -(a  +  c))  and  (r0  <  a))
Date html generated:
2020_05_20-PM-00_33_46
Last ObjectModification:
2019_11_11-PM-00_18_28
Theory : reals
Home
Index